English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Graph each system of equations and state its solution.
y=(3/2)x + 19/2
x - y = -7

A (0, -2)
B (-3, 2)
C (-5, 2)
D (2, 5)
E (-2, -4)
F No Solution

2007-07-03 09:06:13 · 3 answers · asked by Nathan C 1 in Science & Mathematics Mathematics

3 answers

We can't really graph them for you, so you're on your own there.

Draw each one on the same graph and see where they intersect. (The answer is C)

2007-07-03 09:09:36 · answer #1 · answered by Mathematica 7 · 0 0

[C] is the correct answer:

As user (Mathematica) said, we can't make a graph here but what you need to do is just to draw a cartesian coordinates with two axes of x and y and give two arbitrary points in each equation to draw the lines.

For the first equation: (x_1, y_1) & (x_2, y_2)
and for the second equation: (x_3, y_3) & (x_4, y_4)

For instance you may plug (x_1 = 0) in the first equation and you will find (y_1 = 9.5) and you may plug (x_2 = - 4) and you get (y_2 = 3.5) then you draw the first line.

For the second line, you may plug (x_3 = 0) and you get (y_3 = 7) and you may plug (x_4 = -4) and you get (y_4 = 3). Now you draw the second line.

Then what you need is a ruler to extend both lines in a way to intersect each other and you will see the intersection point.

A quick solution is just to plug in the answers one by one into the second equation (x - y) = -7 which is simpler equation.

A: when you plug x = 0 and y = -2,
0 - (-2) = 2
It does not satisfy the equation! It should be -7 if the point is on the line in the second equation!
So [A] is incorrect!

B: x = -3 and y = 2 so again
-3 - 2 = -5 ! Not (-7)
So [B] is incorrect!

C: x = -5 and y = 2 so
-5 - 2 = -7 !
So [C] can be the correct answer!

D: x = 2 and y = 5 so again
2 - 5 = -3 ! Not (-7)
So [D] is incorrect!

E: x = -2 and y = -4 so again
-2 - (-4) = 2 ! Not (-7)
So [E] is incorrect!

Now you plug the only possible correct answer (-5, 2) into the first equation to see if it satisfy the equation:
x = -5 and y = 2 so
2 = (3/2) * (-5) + (19/2) = (-15/2) + (19/2) = (-15 + 19)/2 = 4/2 = 2!

So certainly [C] is correct answer!

For an analytical solution to this, you may do this:

You have these two equations:
y = (3/2)x + 19/2 (eq - 1)
x - y = -7 (eq - 2)

(eq - 2) can be written as: y = x + 7
So to intersect we need to equal the "y" in both equations:So you have:

x + 7 = (3/2)x + 19/2

then:
(3/2)x - x = 7 - (19/2) which gives you:
((3-2)/2)x = ((14-19)/2) so:
(1/2)x = (-5/2) so

x = -5

Then you insert (x = -5) in either equations (eq-1 or eq-2) and you get the "y" for the intersection:

For instance you insert (x = -5) in (eq-2) which is simpler and you get:

(-5) - y = -7 which gives you: y = (-5) + 7 and that finally gives you "y" as:

y = 2

So the intersection point is: ( -5 , 2) which is the answer in [C]

2007-07-03 16:26:59 · answer #2 · answered by Arash S 2 · 0 0

2y = 3x + 19

3x - 2y = - 19
x - y = - 7

3x - 2y = - 19
- 2x + 2y = 14---ADD
x = - 5

10 + 2y = 14
2y = 4
y = 2

x = - 5 , y = 2
ANSWER C

2007-07-07 02:53:39 · answer #3 · answered by Como 7 · 0 0

fedest.com, questions and answers